2009
DOI: 10.1088/1126-6708/2009/07/026
|View full text |Cite
|
Sign up to set email alerts
|

Exact gravity dual of a gapless superconductor

Abstract: A model of an exact gravity dual of a gapless superconductor is presented in which the condensate is provided by a charged scalar field coupled to a bulk black hole of hyperbolic horizon in asymptotically AdS spacetime. A critical temperature exists at which the mass of the black hole vanishes and a scaling symmetry emerges. Below the critical point, the black hole acquires its hair through a phase transition while an electromagnetic perturbation of the background Maxwell field determines the conductivity of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 36 publications
(68 reference statements)
1
54
0
Order By: Relevance
“…where a prime denotes the derivative with respect to r. At the event horizon r = r + of the black hole, we must have 8) and at the asymptotic AdS region (r → ∞), the solutions behave like…”
Section: Einstein-gauss-bonnet Ads 5 Black Hole and Superconductormentioning
confidence: 99%
See 1 more Smart Citation
“…where a prime denotes the derivative with respect to r. At the event horizon r = r + of the black hole, we must have 8) and at the asymptotic AdS region (r → ∞), the solutions behave like…”
Section: Einstein-gauss-bonnet Ads 5 Black Hole and Superconductormentioning
confidence: 99%
“…The AdS/CFT duality is a powerful tool for investigating strongly coupled gauge theories, the application might offer new insight into the study of strongly interacting condensed matter systems where the perturbational methods are no longer available. Therefore, much attention has been given to the studies of the AdS/CFT duality to condensed matter physics and in particular to superconductivity recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In these studies most of the holographically dual descriptions for a superconductor are based on a model that a simple Einstein-Maxwell theory coupled to a charged scalar.…”
Section: Introductionmentioning
confidence: 99%
“…In the gauge/gravity duality, the nontrivial dilaton profile can be identified with the running coupling constant of the dual gauge theory. It was also shown that the nontrivial dilaton coupling of the gauge fluctuation plays an important role to determine the properties of the dual gauge theory leading to the strange metallic behavior [20,21,23,30,54,55,56]. Therefore it is, indeed interesting to study hydrodynamic properties of the vector fluctuations with or without a nontrivial dialton profile.…”
Section: Properties Of the Non-conformal Dual Gauge Theorymentioning
confidence: 99%
“…In this system a scalar condensate can take place through the coupling of the scalar field with the Maxwell field. Much attention has been focused on the application of AdS/CFT correspondence to condensed matter physics since then [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%